MANAJEMEN RISIKO PERBANKAN DAN DUGAAN TINDAKAN PERJANJIAN TERTUTUP (TYING AGREEMENT) DALAM KEGIATAN KERJASAMA BANCASSURANCE ANTARA BANK DAN ASURANSI - Diana Fitriana (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2017)
Insurance companies develop marketing strategies in cooperation with the Bank as a partner. This collaboration is called Bancassurance, which according to the SEBI (Bank Indonesia Circular) No. 12/35 / DPNP on December 23, 2010 had some kind. Furthermore, it is known that there are kinds of bancassurance are included in the category of pure bundling product or often referred to tying.Such bundling categories included in the agreement which is prohibited under Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. Having regard to the conditions of the insurance company's market share at this time, then the pure product bundling or tying in bancassurance is said to be in violation of the competition law and has the potential for very little to say can create monopolistic practices and unfair competition in violation of Law No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. Bancassurance partnership in the form of this, it is possible that the existence of the business risks that occur, in this thesis also describes how the Bank's risk management in the face of the type of business cooperation with insurance companies or also called Bancassurance. The importance of risk management for the bank in the form of further bancassurance cooperation is seen as an issue that needs to be studied seriously. This is because the position of the bank, which generally only as a dealer and can not be held if at a later appeared on the legal issue of insurance products distributed by the bank or the products are packaged in a bundle of products between the bank and insurance is concerned. In terms of minimization of the bank's own liability associated with the efforts of separation between banks and insurers are particularly stringent in countries that do not adhere to the universal banking system. Research in this thesis using the method of normative legal research or library research (library research). Through this method, researchers examined and analyzed the library materials and documents relevant to the substance of the research. Normative legal research is research that examines the law as a positive norm (as it is written in the book). Keywords: Bancassurance, Risk Management and Tying Agreement.